MERANCANG SEJARAH GEREJA YANG SOLIDER - Rafael Isharianto (Litbang STFT Widya Sasana Malang, 2003)
The effect of the Dutch colonialism in Indonesia can still be observed in the historiography on the Indonesian Churches. It is partly due to the fact that the colonialism was closely related to christian missions. After the proclamation of the Indonesian Independence, the progress of the Indonesian nationalism has influenced the way of the historians to chart the history of Indonesian, as well as that of the Catholic Church, in the light of this conception. In this article, we will reflect on the meaning of the historical truth by taking into consideration some ideas in the political theology in so far as these can be observed in the reflections of J.B. Metz. And in so doing, we intend to learn how to prevent ourselves from proclaiming that we have the historical truth.